Vers un marché régional du logement : le cas de la promotion à but non lucratif dans la région métropolitaine de Vienne - Aurore Meyfroidt (Métropoles)
This article explores the territorialisation of housing policies by focusing on a specific type of developer - non-profit housing associations - in an iconic area: the Viennese region. In spite of rigid administrative boundaries within a region comprising three Länder (states), non-profit housing, which has existed here since the end of the 19th century, helps to achieve silent integration in the region by spreading out housing development and enabling the emergence among developers of new cooperation practices beyond infra-regional limits.